2021
DOI: 10.1002/jgt.22729
|View full text |Cite
|
Sign up to set email alerts
|

Highly edge‐connected regular graphs without large factorizable subgraphs

Abstract: We construct highly edge‐connected r‐regular graphs of even order which do not contain r − 2 pairwise disjoint perfect matchings. When r is a multiple of 4, the result solves a problem of Thomassen [4].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…For large k, we made use of Theorem 3 in [26] to find a realization with a k-factor that has many edge-disjoint 1-factors. However, this approach maybe limited since Mattiolo [18] K t I t+2 Along with requiring the connectivity of a graph G and it's complement G, Ando et al [1] showed that bounding the difference of the maximum degree and minimum degree of G would yield a 1-factor in either G or G. Ignoring the connectivity requirement we are able to show that bounding the difference d 1 − d n for a non-increasing degree sequence (d 1 . .…”
Section: Theorem 2 ([10]mentioning
confidence: 83%
“…For large k, we made use of Theorem 3 in [26] to find a realization with a k-factor that has many edge-disjoint 1-factors. However, this approach maybe limited since Mattiolo [18] K t I t+2 Along with requiring the connectivity of a graph G and it's complement G, Ando et al [1] showed that bounding the difference of the maximum degree and minimum degree of G would yield a 1-factor in either G or G. Ignoring the connectivity requirement we are able to show that bounding the difference d 1 − d n for a non-increasing degree sequence (d 1 . .…”
Section: Theorem 2 ([10]mentioning
confidence: 83%
“…We also need the following lemma, whose proof is basically the same as that of Lemma 2.4 in [12] but its statement is more general. To keep the paper self-contained, the proof is presented.…”
Section: Figurementioning
confidence: 99%
“…In this section we construct a (4k +2)-edge-connected (4k +2)-graph G k without a 4k-PDPM for each integer k ≥ 1. As in [12], we first construct a graph P k by adding perfect matchings to the Petersen graph and a graph Q k by using two copies of P k . Then, we construct a graph S k and "replace" some edges of S k by copies of Q k to obtain the graph G k with the desired properties.…”
Section: Proof Of Theorem 13mentioning
confidence: 99%
“…Some of those restrictions may not be necessary as in the same paper Thomassen posed some nice conjectures and problems that lift them. However, Mattiolo [17], answering Problem 1 in [21], presented k-regular k-edge-connected graphs that cannot be partitioned into a 2-factor and k − 2 1-factors. Thus, our strategy maybe limited to finding many edge-disjoint 1-factors, but not k of them.…”
Section: Theorem 7 ([1]mentioning
confidence: 99%